Students’ Perception toward the Implementation of Synchronous Learning during COVID-19 Pandemic in English Language Teaching (ELT) - Tira Nur Fitria (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2021)
Abstract. During COVID-19 pandemic, educators implement online learning in the education process. Basic interactive models of online learning available, such as synchronous learning, as a face-to-face learning process through online media. This research investigates the students’ perception toward the implementation of synchronous learning in ELT especially TOEFL. This research is qualitative. The results show that: 1) 51 % of students use Zoom and Live YouTube in learning TOEFL. 2) 89.7 % of students use mobile phones in online learning. 3) 49.7 % of students agree that Zoom has complete features. 4) 83.2 % of students agree that operating Zoom’s features is very easy. 5) 74.2 % of students agree that Zoom is easy-used. 6) 72.9 % of students agree that using Zoom in learning TOEFL is effective. 7) 73 % of students agree that using Live YouTube in learning TOEFL also effective. 8) 63.9 % agree that in Zoom, they can participate by face-to-face interactions (e.g. question-answer even discussion with lecturer and classmates. 9) 95.5 % of students agree that using YouTube, videos can be seen anytime and anywhere because videos are stored on the lecturer’s channel. In the understanding level of TOEFL, 83.2 % of students really understand in the listening section, 89.7 % of students understand the reading section, and 81.3 % of students understand the Structure and Written Expression section. Several problems affect learning TOEFL with Zoom and YouTube. Students have a problem with an internet connection. The other problems are internet quota, technical problems of the device (e.g battery, device dead suddenly, audio quality, device’s video/audio, and others), device’s type used, and surrounding conditions (e.g light conditions, sounds, or other disturbances). In the next learning system, 80.6 % of students agree that the next learning system implements face-to-face learning and still uses Zoom and YouTube Live Streaming. Keywords: ELT, synchronous learning, TOEFL, YouTube, Zoom Abstrak. Selama pandemi COVID-19, para pendidik menerapkan pembelajaran online dalam proses pendidikan. Model pembelajaran online interaktif dasar yang tersedia, seperti pembelajaran sinkron, sebagai proses pembelajaran tatap muka melalui media online. Penelitian ini mengkaji persepsi siswa terhadap penerapan pembelajaran sinkron di ELT khususnya TOEFL. Penelitian ini bersifat kualitatif. Hasil penelitian menunjukkan bahwa: 1) 51% siswa menggunakan Zoom dan Live YouTube dalam pembelajaran TOEFL. 2) 89,7% siswa menggunakan ponsel dalam pembelajaran online. 3) 49,7% siswa setuju bahwa Zoom memiliki fitur yang lengkap. 4) 83,2% siswa setuju bahwa mengoperasikan fitur Zoom sangat mudah. 5) 74,2% siswa setuju bahwa Zoom mudah digunakan. 6) 72,9% siswa setuju bahwa menggunakan Zoom in learning TOEFL efektif. 7) 73% siswa setuju bahwa menggunakan Live YouTube dalam pembelajaran TOEFL juga efektif. 8) 63,9% setuju bahwa dengan Zoom, mereka dapat berpartisipasi dengan interaksi tatap muka (misalnya tanya jawab bahkan diskusi dengan dosen dan teman sekelas. 9) 95,5% mahasiswa setuju bahwa dengan menggunakan YouTube, video dapat dilihat kapan saja dan di mana saja karena video disimpan di saluran dosen. Pada tingkat pemahaman TOEFL, 83,2% siswa sangat memahami bagian menyimak, 89,7% siswa memahami bagian membaca, dan 81,3% siswa memahami bagian Struktur dan Ekspresi Tertulis. Beberapa masalah memengaruhi pembelajaran TOEFL dengan Zoom dan YouTube. Siswa memiliki masalah dengan koneksi internet. Masalah lainnya adalah kuota internet, masalah teknis perangkat (misal baterai, perangkat mati mendadak, kualitas audio, video/audio perangkat, dan lain-lain), jenis perangkat yang digunakan, dan kondisi sekitarnya (misal kondisi cahaya, suara, atau gangguan lainnya). Pada sistem pembelajaran selanjutnya, 80,6% siswa setuju bahwa sistem pembelajaran selanjutnya menerapkan pembelajaran tatap muka dan masih menggunakan Zoom dan YouTube Live Streaming.Kata kunci: ELT, pembelajaran sinkronus, TOEFL, YouTube, Zoom